ChemInform Abstract: Palladium‐Catalyzed Formal Hydroacylation of Allenes Employing Carboxylic Anhydrides and Hydrosilanes. Issue 42 (October 2015) - Fujihara, Tetsuaki; Hosomi, Takuro; Cong, Cong; Hosoki, Tomoya; Terao, Jun; Tsuji, Yasushi
Abstract Title reaction provides access to α, β‐unsaturated ketones in a highly regio‐ and E/Z‐selective manner.